'The centre of the muniment': archival order and reverential historiography in the India Office, 1875. (January 2019) - Mitchell, Peter; Lester, Alan; Boehme, Kate
Abstract: In 1875, the civil servants and scholars George Birdwood and Clements Markham both submitted proposals to the India Office regarding the cataloguing and arrangement of its archive. These proposals had in common that they both involved the records of the early modern East India Company, and evinced an understanding of the archive as both a privileged repository of historical artefacts and a technology of imperial government. However, they articulated divergent ideologies of empire, ways of conceptualising the past and its materials, and understandings of the ways in which information and knowledge should be mobilised in an imperial context. This article analyses the two proposals in the light of their proposers' biographies, their politics, and their institutional and disciplinary commitments; and it notes each proposal's contribution to the production of a historiography which valorized early modern navigators, traders and mercantile communities as progenitors of the British imperial state. The proposals' troubled bureaucratic history emerges as an expression of conflicts of practice, ideology and administrative cultures within the India Office, and more broadly within the imperialisms of the time. Highlights: Considers two proposals for reorganising the English East India Company archive in the 1870s. Traces the development of reverential historiographies of early modern empire. Explores late Victorian imperial historiographies as sites of ideological contest. Demonstrates how these conflicts affected the disciplinary formation of geography and history.